2010
DOI: 10.1007/s11295-010-0347-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mapping in Pinus: sugar pine (Pinus lambertiana Dougl.) and loblolly pine (Pinus taeda L.)

Abstract: The majority of genomic research in conifers has been conducted in the Pinus subgenus Pinus mostly due to the high economic importance of the species within this taxon. Genetic maps have been constructed for several of these pines and comparative mapping analyses have consistently revealed notable synteny. In contrast, little genomic research has been conducted on the Pinus subgenus Strobus, even though these pines have strong ecological relevance. We report a consensus genetic linkage map for sugar pine (Pinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
(47 reference statements)
0
38
0
Order By: Relevance
“…A major "gene" of resistance (MGR) to WPBR was mapped in P. lambertiana over 40 years ago (Kinloch 1970). An apparently biallelic locus, Cr1 R /Cr1 r locus has been mapped in several P. lambertiana families (Devey et al 1995;Harkins et al 1998;Jermstad et al 2011). In this work, we leverage these markers and the 1614 K. A. Stevens et al…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A major "gene" of resistance (MGR) to WPBR was mapped in P. lambertiana over 40 years ago (Kinloch 1970). An apparently biallelic locus, Cr1 R /Cr1 r locus has been mapped in several P. lambertiana families (Devey et al 1995;Harkins et al 1998;Jermstad et al 2011). In this work, we leverage these markers and the 1614 K. A. Stevens et al…”
mentioning
confidence: 99%
“…RNA sequencing was done using Illumina MiSeq and HiSeq to generate short (100-300 bp) reads, and PacBio Iso-Seq reads, which range from 1000 to over 6000 bp. Identification of genomic scaffolds and mapping in the Cr1 region Jermstad et al (2011) reported the sequences from cloned RAPD bands OP_G16 and BC_432 that were linked to Cr1. To identify these genomic loci, the representative consensus sequence for each RAPD band was aligned to the P. lambertiana genome assembly using gmap (Wu and Watanabe 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has generated thousands of markers for genetic mapping, significantly improving our understanding of large and complex conifer genomes (Jermstad et al 2011;Pavy et al 2012;Mart ınez-Garc ıa et al 2013;Neves et al 2014). We show here that a combination of highly multiplexed SNP genotyping and a selective mapping strategy is useful for the cost-efficient mapping of hundreds of genes, as the bin set of 92 highly recombinant F2s represented 95% of the recombination occurring among the initial set of 477 genotypes used to construct the framework linkage map.…”
Section: Linkage and Qtl Mappingmentioning
confidence: 99%
“…In more species chromosomal information is need for understand of species relationships in respect to chromosomes in a large genus Pinus. On the other hand the genome studies are progressing in several pine species of P. radiate (Kuang et al 1999), P. thumbergii (Kondo et al 2000), P. contorta (Li and Yeh 2001), P. elliottii (Brown et al 2001), P. pinaster (Chagné et al 2003), P. sylvestris (Hurne et al 2000;Komulainen et al 2003), P. densiflora (Kim et al 2005), P. taeda (Echt et al 2011;Martínez-García et al 2013), P. lambertiana (Jermstad et al 2011) and P. balfouriana (Friedline et al 2015) and their genome maps are constructed by various molecular markers such as AFLPs, RFLPs, RAPDs, ESTPs, cDNA and SSRs and compared among species in respect to synteny (see Jermstad et al 2011). In pine genome study correspondence between individual chromosomes and linkage groups of genetic map is not established in Pinus.…”
Section: Abstract: Chromosome Diploxylon Pine Fluorescent Band Karmentioning
confidence: 99%